2021
DOI: 10.3390/ijerph18105106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Life Space Extent and Apathy: A Comparison of Competitive Japanese Swimmers with and without Disabilities

Abstract: Changes in the daily lives and mental health of people with disabilities due to the coronavirus disease (COVID-19) pandemic have not been reported. The Japanese government closed public facilities, including swimming pools, during the first wave of COVID-19, and many competitive swimmers lost their places of activities. This study aimed to investigate the impact of the COVID-19 pandemic on life space and apathy among swimmers and investigated differences in the impact on swimmers with and without disabilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Collective evidence from Europe (13,55–63), Asia (64,65), Canada (66), South America (67), and the Middle East (68–70) is demonstrating that the pandemic-related restrictions had clear negative impact on mental well-being among athletes across all ages. Surveys administered one to three times during the pandemic have identified mood disturbances, behavioral changes, and varying levels of stress among competitors ranging in age from youth, collegiate through professional.…”
Section: Mental Health Impact Of Covid On Athletesmentioning
confidence: 99%
“…Collective evidence from Europe (13,55–63), Asia (64,65), Canada (66), South America (67), and the Middle East (68–70) is demonstrating that the pandemic-related restrictions had clear negative impact on mental well-being among athletes across all ages. Surveys administered one to three times during the pandemic have identified mood disturbances, behavioral changes, and varying levels of stress among competitors ranging in age from youth, collegiate through professional.…”
Section: Mental Health Impact Of Covid On Athletesmentioning
confidence: 99%
“…Focusing on mental health, one study on para-swimmers showed decreased apathy in female swimmers compared to their able-bodied pairs during state of emergency. This was elevating again after restrictions were eased (Kaneda et al, 2021 ). Furthermore, para-athletes expressed their concerns about their health and their social contacts during the pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interrupted preparation, sport adaptation could be impacted with fears of a deterioration in performance. Moreover, during the COVID-19 pandemic, only emergency care was available, performance testing such as CPET was postponed [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%